Querelle de minarets en Égypte. Le débat public sur l’appel à la prière - Iman Farag (Revue des Mondes Musulmans et de la Méditerranée)
In the middle of the first decade of the 21st century, Egyptian authorities decided to unify the call to prayer (azan). Several arguments were presented dealing with urban disorder, sound pollution and the disrespect of religious practice. Years later the measure has yet to be adopted. Its announcement however, produced a rich and problematic debate, in which antagonistic opinions shared the same references but were organized in different hierarchies. This article examines the debate from several angles: in form and in content, indissociably, the problem of debate structure is presented as a transformative variable: the respective roles of media choice and the increasing participation of anonymous contributors, represent a challenge for the analyst, and finally, the limits of free speech, which more often depend upon the inconstant vigilance of the morality police than upon defined limits. This also suggests the existence of linkages between the willingness to take a public stand and various other social registers of experience, including “listening” as a sensorial experience and the extent to which azan is identified as a distinctive element in an aural landscape. Further, the question is raised as to technical abstractions and religious fervour elicited and the extent to which these reflect a broader thematic regarding the mechanical reproduction of so-called secular artistic performances.